Analysis of BUKU III bank soundness during the covid-19 pandemic using RGEC method - Suryanto Sosrowidigdo (Enrichment : Journal of Management, 2022)
The Banking industry plays an important role in the economic field. Banks helps circulating money from and to the people. However, because of the COVID-19 Pandemic, the ability of Banks to maintain a stable economy has been tested vigorously. This study aims to find whether BUKU III Banks experienced a difference in their financial performance. This study set up several criteria for its samples and the Banks that meets that criteria are OCBC NISP, BTPN, Permata, Maybank, BTN, Mayapada, Mega, BJB, and Bukopin. This study uses RGEC Method which consists of four indicators, Risk Profile which is proxied by NPL, Good Corporate Governance, Earning, which is proxied by ROE, and Capital which is proxied by CAR. On top of RGEC Analysis, Difference Test was also used to determine whether there was a significant difference in BUKU III Banks’ financial performance. This study uses SPSS 25 to process data. The data used in this research is a secondary data obtained from financial statements on the IDX and respective Banks’ website. The result of this research shows that Risk Profile, proxied by NPL ratio, did not experienced a significant difference in performance. Good Corporate Governance also did not experience a significant difference in performance. Earning, proxied by ROE, did not showed a significant difference in performance. Lastly, Capital, proxied by CAR, showed significant difference in performance.